Strategi Balai Konservasi Sumber Daya Alam (BKSDA) Aceh Dalam Melakukan Penanganan Hilangnya Satwa Langka Di Lokasi Pertambangan Tanpa Izin (Peti) Di Tangse - Iqkram Maulana; Delfi Suganda (Jurnal Administrasi Politik dan Sosial, 2026)
Abstract The loss of endangered wildlife poses a serious threat to biodiversity conservation, particularly in Aceh, which hosts the Leuser Ecosystem as a vital habitat for the Sumatran elephant (Elephas maximus sumatranus), Sumatran tiger (Panthera tigris sumatrae), and Sumatran orangutan (Pongo abelii). Tangse Subdistrict, Pidie Regency, has come under increasing pressure due to the proliferation of illegal mining activities (unlicensed mining/PETI), which cause habitat degradation and heighten the risk of wildlife poaching. In this context, the Aceh Natural Resources Conservation Agency (BKSDA Aceh) plays a crucial role in preventing the loss of endangered species through monitoring and control efforts. This study aims to examine the strategies employed by BKSDA Aceh to prevent the loss of endangered wildlife in the PETI-affected areas of Tangse, as well as to identify the challenges encountered in their implementation. The research adopts a descriptive qualitative approach using interviews, observation, and documentation. Keywords: endangered species, BKSDA Aceh, illegal mining (PETI), conservation strategy